Responsabilidad ética en los medios de comunicación: Caso diario digital La Hora Regional - Ciza Haro, Jefferson Salvador (2022)
The present case study focused on the ethical responsibility of the media: Case of the digital newspaper la Hora regional. Currently, ethics is considered as one that has the ability to identify good acts from bad morally speaking, the fulfillment of ethical responsibility is something that is beyond the reach of the human being. The importance of social responsibility (SR) in the media is a subject that is in constant debate inside and outside the media itself. The SR of the media is directly related to the impact that its content can have on the public or citizens. Undoubtedly the most relevant is the power that the media have in shaping public opinion. Within the research line of the Social Communication career at the Technical University of Babahoyo is the sub-line of research of the career: Deontology and Responsible Journalism. The media are the entities responsible for providing impartial information to society. Therefore, the media must have criteria of impartiality, public interest and citizen demand. The objective of this study was to analyze the ethical responsibility of the digital newspaper La Hora Regional during the year 2021. The research methodology based on a descriptive study was used. The information analyzed was through interviews with communication professionals, in order to seek information presented by the medium on this social problem. Once the case study is completed, it can be determined that the digital newspaper La Hora has responsibility and ethics.